The Use of Ruang Bahasa I.d Youtube Channel in VII Class Learning Letter Text Material - Hesty Wahyu Asima; I Made Sutama; I Gede Nurjaya (STAI Hubbulwathan Duri, 2022)
This research aims to describe the planning, implementation, and obstacles in letter text learning using the Youtube video of Ruang Bahasa I.d channel in VII class of UPT SMP Negeri 3 Ponggok. The subjects of this research are students of class VII D UPT SMP Negeri 3 Ponggok, while the object of this research is the use of the Youtube channel of Ruang Bahasa I.d in letter text learning. This research used a qualitative descriptive design. The method used in collecting data is observation and interviews. For data analysis techniques, this research used the Miles and Huberman technique. The results showed that five letter text learning plans are using the Ruang Bahasa I.d, namely (1) reviewing the syllabus, (2) looking for learning media, (3) reviewing the media to be used, (4) making evaluation materials, and (5) making RPP. The implementation of learning has several stages, namely (1) opening, (2) doing apperception, (3) sending Youtube links, (4) viewing the video, (5) doing discussions, (7) the teacher providing affirmations and conclusions, and (7) the teacher closes the learning. The obstacles felt by the teacher were (1) some students did not have an internet quota, (2) teachers can't control students to view video seriously, (3) the students' responses were less than face-to-face learning, and (4) some students are late for class. However, despite many obstacles, the learning that has been carried out is better than learning that only uses modules.